2018
DOI: 10.3928/01484834-20180921-05
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research Nursing: Awareness and Understanding Among Baccalaureate Nursing Students

Abstract: Background: The American Nurses Association recognizes the specialty practice of Clinical Research Nursing, but many new nurses are unaware of the specialty and lack knowledge to effectively interact with research teams. Method: Participants completed a novel online survey to describe the level of awareness and understanding of the clinical research nursing specialty and the effect of clinical studies on nursing practice in fourth-year baccalaureate nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The speciality practice of clinical trial nurse has been recognised by the American Nurses Association and IACRN (IACRN, ) and moves to promote this are being pursued in the UK, Ireland and Taiwan (Hill, ). In tandem with this, it is argued that nurse education programmes should better prepare students on what the CRN role involves and the importance of clinical research knowledge to nursing practice (Alsleben, Alexander, & Matthews, ).…”
Section: Discussionmentioning
confidence: 99%
“…The speciality practice of clinical trial nurse has been recognised by the American Nurses Association and IACRN (IACRN, ) and moves to promote this are being pursued in the UK, Ireland and Taiwan (Hill, ). In tandem with this, it is argued that nurse education programmes should better prepare students on what the CRN role involves and the importance of clinical research knowledge to nursing practice (Alsleben, Alexander, & Matthews, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals who find a career in clinical research are poorly prepared for their roles, given the paucity of academic content about clinical research in undergraduate college and nursing programs and are trained “on the job” (Sonstein et al, 2014; Carter et al, 2007). Moreover, nursing students have difficulty distinguishing role differences between nurse researchers and clinical research nurses (Alsleben et al, 2018) or that a career trajectory for clinical research nurses exists (Kunhunny and Salmon, 2017). Nevertheless, the likelihood of nurses encountering and caring for patients who are involved in clinical trials is a reality that should not be under-emphasized (Eckardt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to the density of the baccalaureate nursing curricula (Galassi et al, 2014; Garner et al, 2016). Alsleben et al, (2018) pointed out that another contributing factor in deterring nursing students from becoming CRNs is the lack of awareness of the growing CRN specialty (Alsleben et al, 2018). Similarly, clinical research is often missed during staff development training for hospital nurses (Galassi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even so, nurse–researchers sometimes worry that vulnerable populations might not be able to provide informed consent or that participating in a study would create more psychological or physiological harm than good (Newman et al, 2017; Taua et al, 2014). Despite this, Alsleben et al (2018) found that although nurse–researchers often feel they must act as gatekeepers when conducting research with vulnerable populations, participants incurred little harm as a result. Those who have the opportunity are likely to benefit and participate.…”
Section: Introductionmentioning
confidence: 99%